Development of pharmacovigilance training module for community pharmacists in Nepal: A focus group study - Subish Palaian; Mohamed Izham Mohamed Ibrahim; Pranaya Mishra (Archives of Global Professionals, 2016)
Objective: We assessed the feedback from community pharmacists on training sessions on adverse drug reaction (ADR) reporting provided by the regional pharmacovigilance center. In addition, we examined the relationship between feedback scores and demographic characteristics of the community pharmacists. Methods: The training on ADR reporting was divided into three sessions. Each session lasted for 1-2 h duration, spanning over 6 months. A questionnaire was provided to obtain feedback on the training sessions. The questionnaire had a total of twenty questions on a 5-point Likert scale (maximum possible total score could be 100). The feedback scores obtained were compared with a demographic profile. Mann-Whitney U-test was used for comparing the scores of the subgroups with "two groups" and Kruskal-Wallis test for the subgroups with more than two groups. P < 0.05 was considered statistically significant. Results: Most of the pharmacists participated were male (n = 18), aged between 31 and 40 years (n = 14), with educational qualifications of community medical assistant (n = 12) and length of experience in community pharmacy between 1 and 5 years (n = 14). The overall median (interquartile range) of the responses was 79 (73.5-81.0); the maximum possible score was 100. There was no association between the total scores and gender, age, educational qualifications, and length of experience in the community pharmacy. Conclusions: The feedback revealed that participants find the training sessions were useful and they were interested in future sessions. Educational interventions can play an important role in improving ADR reporting.